Un puñado de vida - Daniela Alcívar Bellolio (Cuadernos LIRICO)
The difference between life and biography is the same that exists between the generality of language and the irreducibility of experience, one that tenses the possibilities of expression and representation. This article starts from that tension in order to think about the place of crisis (illness, betrayal, grief) in writing, with focus on Melanoma, a book of short stories by the argentine writer Andrea Rabih.